ANALISA PENGARUH VARIASI KONSENTRASI PELAPISAN POLYSILAZANE PADA PERMUKAAN SUDU TURBIN SS 410 DALAM PENINGKATAN SIFAT MEKANIK - PAKHRI MANARUL, HIKAM; IRWAN, YUSRIL; ARNALDO, M. HANS (e-Proceeding FTI, 2024)
The steam turbine blade is the main component in the steam turbine which experiences wear due to friction with the flowing hot fluid. Apart from that, turbine blades also experience corrosion due to the acid content contained in the steam and erosion due to high pressure. To overcome this problem, the surface of the steam turbine blade will be coated with organic and inorganic polysilazane. Tests that will be carried out to determine the performance of the polysilazane layer on the turbine blade include hardness testing with a pencil hardness test, analyzing the adhesion of the coating with the Cross Cut Adhesion test and to determine the adhesive strength of the film formed from the polysilazane reaction using a scanning electron microscope on the substrate. Abstrak Sudu turbin uap adalah komponen utama dalam turbin uap yang mengalami keausan akibat gesekan dengan fluida panas yang mengalir. Selain itu sudu turbin juga mengalami korosi akibat kandungan asam yang terkandung pada uap dan erosi akibat tekanan tinggi. Untuk mengatasi masalah tersebut, permukaan sudu turbin uap akan dilapisi dengan Organik dan Inorganik Polysilazane. Pengujian yang akan dilakukan untuk mengetahui performa lapisan polisilazane pada sudu turbin antara lain pengujian kekerasan dengan pencil hardness test, menganalisa daya rekat lapisan dengan Cross Cut Adhesion test dan untuk mengetahui daya rekat film yang terbentuk dari reaksi polysilazane melalui scanning electronmicroscope terhadap substrat.